An Integrative Management Model for Islamic Boarding Schools: Enhancing Religious Education through Systemic Governance - Maisah; Fadlilah; Zulfa Rahmat Hidayati; Muhammad Zaki Rahman (Al-Qalam Institue, 2026)
This study aims to analyze pesantren management practices in developing Islamic Religious Education (PAI) and to formulate an integrative management model that enhances the effectiveness and sustainability of PAI implementation in Islamic boarding schools. This research employed a qualitative approach with a case study design. Data were collected through observations, semi-structured interviews, and document analysis. The collected data were analyzed using an interactive analysis model consisting of data condensation, data display, and conclusion drawing and verification. The findings indicate that effective pesantren management is developed through the integration of planning, organizing, implementation, and supervision, supported by curriculum integration, teacher development, student character formation, religious habituation, and educational activities. PAI implementation extends beyond classroom instruction by facilitating the internalization of Islamic values, including faith, worship, morality, discipline, responsibility, and leadership. This study proposes an Integrative Management Model for Islamic Boarding Schools in the Development of Islamic Religious Education, which provides a conceptual and practical framework for strengthening pesantren governance and improving the quality of Islamic Religious Education.